2013
DOI: 10.1088/0957-4484/24/32/325202
|View full text |Cite
|
Sign up to set email alerts
|

Gradual electroforming and memristive switching in Pt/CuOx/Si/Pt systems

Abstract: We report a memristive switching effect in Pt/CuOx/Si/Pt devices prepared by the rf sputtering technique at room temperature. Differently from other Cu-based metal filament switching systems, a gradual electroforming process, marked by a gradual increase of the device resistance and a gradual decrease of the device capacitance, was observed in the current-voltage and capacitance characteristics. After the gradual electroforming, the devices show a uniform memristive switching behavior. By Auger electron spectr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A wide assortment of oxides, higher chalcogenides (compounds of S, Se, Te), halides, and other insulating materials have been used in CBRAM-like devices [19]. These compounds generally fall into three categories; (ion) electrolytes, such as AgI and related materials [20][21][22][23][24] and Ag-polymer [25]; mixed (ion-electron) conductors such as Ag 2+δ S [18,26,27], Cu 2−δ S [28,29], Cu 2−δ O [30][31][32], Ag-AsS x [33,34], Ag-GeSe x [9,35], Cu-GeSe x [36,37], Ag-GeS x [38,39], Cu-GeS x [38,40], Cu-GeTe [41], Cu-TCNQ [42,43], and a-Si [44][45][46]; and insulators that are not ordinarily considered as solid electrolytes such as SiO 2 [47][48][49][50], Al 2 O 3 [51,52], WO 3 [53][54][55][56], Ta 2 O 5 [57,58], TiO 2 [59], GeO x [60], ZrO 2 [61], HfO 2…”
Section: Materials Systemsmentioning
confidence: 99%
“…A wide assortment of oxides, higher chalcogenides (compounds of S, Se, Te), halides, and other insulating materials have been used in CBRAM-like devices [19]. These compounds generally fall into three categories; (ion) electrolytes, such as AgI and related materials [20][21][22][23][24] and Ag-polymer [25]; mixed (ion-electron) conductors such as Ag 2+δ S [18,26,27], Cu 2−δ S [28,29], Cu 2−δ O [30][31][32], Ag-AsS x [33,34], Ag-GeSe x [9,35], Cu-GeSe x [36,37], Ag-GeS x [38,39], Cu-GeS x [38,40], Cu-GeTe [41], Cu-TCNQ [42,43], and a-Si [44][45][46]; and insulators that are not ordinarily considered as solid electrolytes such as SiO 2 [47][48][49][50], Al 2 O 3 [51,52], WO 3 [53][54][55][56], Ta 2 O 5 [57,58], TiO 2 [59], GeO x [60], ZrO 2 [61], HfO 2…”
Section: Materials Systemsmentioning
confidence: 99%
“…Similar to ECM, the VCM shows a bipolar and filamentary switching behavior. In recent years many experimental and theoretical studies have reported on the microscopic mechanisms of both the ECM and the VCM, such as probing the structure and composition, [9][10][11][12][13] observing shape evolution, [14][15][16][17] and modeling the connection/disconnection kinetics of the local conductive region. [18][19][20][21] Recently, Valov et al demonstrated that the redox processes are also involved and responsible for the resistance switching in some typical VCM devices, where anodic passivation of the reversible metal electrode takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Copper oxide can show both unipolar and bipolar resistive switching behaviors. In addition, there ismovement of positive Cu + ions or negative O 2− ions (or V o s); formation of filaments are responsible for resistive switching behavior in copperoxide-based ReRAMs [39,40]. Our device showed reproducible and reliable bipolar resistive switching.…”
Section: Resultsmentioning
confidence: 82%